Pemberian Terapi Musik dalam Mengurangi Nyeri Pasien Kanker - Monika Rini Puspitasari; Agung Waluyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to evaluate in the literature whether music therapy can reduce pain in cancer patients. This research method uses an online search for library sources limited to 2016-2021. The databases used include EBSCO, Sage, and Pubmed in English. The results obtained are five research articles analyzed. The results showed that music therapy could be used in pain management in patients with cancer pain. In conclusion, music therapy can help reduce the pain scale that is felt to increase the comfort and quality of life of cancer patients so that the sufferer's quality of life will improve. Keywords: Cancer, Music Therapy, Pain